Analytic Methods for Solving Higher Order Ordinary Differential Equations - Maria P. Beccar-Varela; Md Al Masum Bhuiyan; Maria C. Mariani; Osei K. Tweneboah (Mathematics, 2019)
In this work, an analytic approach for solving higher order ordinary differential equations (ODEs) is developed. The techniques offer analytic flexibility in many research areas such as physics, engineering, and applied sciences and are effective for solving complex ODEs.